PENGARUH PARIWISATA TERHADAP KONDISI SOSIAL BUDAYA MASYARAKAT KARIMUNJAWA, JAWA TENGAH - Thelisa .; Made Budiarsa; Widiastuti . (Magister Tourism Study, Faculty of Tourism, Udayana University, 2018)
This article discusses about the condition of community in Karimunjawa, which at this time Karimunjawa islands became one of the favorite tourist destinations in central Java. Rapid development of tourism in recent years bring signi cant a ects to the condition of the people. This article focuses on the social and cultural aspects of community, aims to explain about development of tourism and to describe the form of socio-cultural changes in Karimunjawa society. A qualitative approach was used to discuss the problems. The data were collected through interviews, observation, and documentation. It was found that tourism in Karimunjawa started when the destination was accessible for tourist. Then, there have been social and cultural change in Karimunjawa community, those are jobs opportunity, division of work, hospitality, education, language skill, lifestyle and social solidarity. These changes have a ected the sustainability of tourism and therefore they need to be directed and managed by all of involved stakeholders in order to maintain the harmonious relationship between community and tourism development.